Un Glyptodontidae de gran tamaño en el Holoceno temprano de la Región Pampeana, Argentina - Soibelzon, Leopoldo Héctor (2012)
We present here the record of a very large glyptodont (1,900 to 2,370 kg); it is a right humerous distal epiphysis (RPCR 1021) coming from the early Holocene (8,480 ± 130 years 14C cal. BP) of the Pampean Region (Los Pozos, Marcos Paz, Buenos Aires Province, Argentina) and we assign it to Doedicurus Burmeister cf. D. Clavicaudatus (Owen). The youngest record for a glyptodont (7,839 ±102 years 14C cal. BP) corresponds to Doedicurus clavicaudatus. Finally we discuss the possible explanations of the great size attained by glyptodonts at the end of the Lujanian age (late Pleistocene-early Holocene).